2008
DOI: 10.1515/hf.2008.033
|View full text |Cite
|
Sign up to set email alerts
|

FT-NIR spectroscopy in predicting the decay resistance related characteristics of solid Scots pine (Pinus sylvestris L.) heartwood

Abstract: FT-NIR spectroscopy equipped with a fiber optic probe was used to predict the mass loss caused by a brownrot fungus (Coniophora puteana) in Scots pine heartwood. Because decay tests are impractical for generating reference data for the calibration of prediction models, the possibilities of using the concentration of heartwood extractives as a reference variable instead of mass loss was studied. The material investigated covered a wide range of natural variation in durability and diffuse reflectance infrared Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Particularly the 475 HW of Scots pine is valued for its properties such as dimensional stability and 476 natural durability. Extractives of HW give, e.g., colour and low hygroscopicity to 477 HW timber and are key determinants of the passive defence, i.e., resistance 478 against degradation of wood by microorganisms (Nakada and Fukatsu, 2012;479 Harju and Venäläinen, 2006;Leinonen et al, 2008 (Magel, 2000;Bergström, 2003;Nakada and Fukatsu, 487 2012). Magel (2000) concluded that the most important contributor for sucrose 488 cleavage was sucrose synthase followed by invertase.…”
Section: Correlation Between Months Of the Year 461mentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly the 475 HW of Scots pine is valued for its properties such as dimensional stability and 476 natural durability. Extractives of HW give, e.g., colour and low hygroscopicity to 477 HW timber and are key determinants of the passive defence, i.e., resistance 478 against degradation of wood by microorganisms (Nakada and Fukatsu, 2012;479 Harju and Venäläinen, 2006;Leinonen et al, 2008 (Magel, 2000;Bergström, 2003;Nakada and Fukatsu, 487 2012). Magel (2000) concluded that the most important contributor for sucrose 488 cleavage was sucrose synthase followed by invertase.…”
Section: Correlation Between Months Of the Year 461mentioning
confidence: 99%
“…160 161 In Scots pine, HW extractives consist of the stilbenes pinosylvin (PS) and 162 pinosylvin monomethyl ether (PSME), resin acids and free fatty acids 163 (Saranpää and Nyberg, 1987). Variation of Scots pine HW phenolic extractive 164 content between tree individuals is wide and strongly correlates with decay 165 resistance of HW (Harju and Venäläinen, 2006;Leinonen et al, 2008). Although 166 extractive content is influenced by the environment (Magel, 2000), it is highly 167 inherited (Fries et al, 2000;Partanen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Schimleck et al (2009) calibrated data concerning density, extractives content, stiffness, and color with NIR spectroscopy. Fungal decay and decay resistance can be recognized by NIR data (Fackler et al 2007;Leinonen et al 2008). Da Silva Perez et al (2007 were able to improve elite tree selection by NIR spectroscopy and genetic tools.…”
Section: Introductionmentioning
confidence: 99%
“…Gierlinger et al 2004a;Kokutse et al 2006;Amusant et al 2008) and wood near-infrared (NIR) spectra (e.g. Gierlinger et al 2003;Sykacek et al 2006;Leinonen et al 2008;Bush et al 2011) have been studied in relation to natural durability and proposed as indirect predictors with more or less success.…”
Section: Introductionmentioning
confidence: 99%